(3cJGH GdbdYis - (3Ydj Hf eMeO Hf CjOeQ GdpLrdnOcj, YR GdOjf,J (B742 (3g` s
(3ChdgG (B:s
(3GYde jG CNj Cf GdbdYi GSeg QUGU hESeg RhGT efShH ddSYO GdCcHQ s
(3BNQgG (B:s
(3aEf GdYdjd HQC ef CSbGeg HgPG GdYdGL jUM efg HEPJ Gddg JYGdi HGdJYOjd GdeRGL hGdSdGe hHg CcedJ cJGH GdbdYi s
(3Vef eLehY s
(3GdPi gh efShH ddeTJQi ai GdebGdI GdQGHYI ef GdLRA GdQGHY efcJGH GdHQgGf ai CSQGQ Yde GdejRGfs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B28s
Keywords: (3GdcjejGA h GdWHjYjGJs